2009
DOI: 10.1007/s12640-009-9038-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and Glial Alterations Due to Focal Cortical Hypoxia Induced by Direct Cobalt Chloride (CoCl2) Brain Injection

Abstract: Ischemic brain injury is a dynamic process that involves oxidative stress, inflammation, and cell death, as well as activation of endogenous adaptive and regenerative mechanisms depending on activation of transcription factors such as hypoxia inducible factor 1-alpha (HIF-1alpha). Because CoCl2 activates HIF-1alpha, we described a new focal-hypoxia model by direct intracerebral CoCl2 injection. Adult male Wistar rats were intracerebrally injected with CoCl2 (2 microl-50 mM), in frontoparietal cortex of right h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…Therefore, we investigated the influence of LXA 4 on HIF-1α protein content in H22 cells. Like in some other tumor cells (38,39), it was also found that HIF-1α was undetectable in control H22 cells but strongly enhanced in cytoplasm and accumulated in nuclei under CoCl 2 -mimiced hypoxic condition. Unlike other antiangiogenic agents that only blockaded VEGF but not HIF-1α (40), we found that CoCl 2 stabilization of HIF-1α was markedly countered by LXA 4 .…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, we investigated the influence of LXA 4 on HIF-1α protein content in H22 cells. Like in some other tumor cells (38,39), it was also found that HIF-1α was undetectable in control H22 cells but strongly enhanced in cytoplasm and accumulated in nuclei under CoCl 2 -mimiced hypoxic condition. Unlike other antiangiogenic agents that only blockaded VEGF but not HIF-1α (40), we found that CoCl 2 stabilization of HIF-1α was markedly countered by LXA 4 .…”
Section: Discussionsupporting
confidence: 61%
“…The severity of this damage was related to the CoCl 2 doses administered, where a fast HIF-1a up-regulation (occurring as soon as 1 h after cobalt injection) was documented (Caltana et al 2009). In several experimental models of cerebral hypoxia, a maximal expression of HIF-1a is observed 5 h after the hypoxic stress, which declines to basal levels at 12 h (Jones and Bergeron 2001;Pascual et al 2001;Stroka et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…All other chemical substances were of analytical grade. CoCl 2 was purchased from (Sigma) and 50 mM solution was freshly prepared as previously described (Lazarowski et al 2007a;Caltana et al 2009). …”
Section: Chemicals and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low glucose, high glucose, and hypoxic media were prepared according to previous reports [18,19] LG+Hypoxia and HG+Hypoxia) [23][24][25].…”
Section: Culture Of Hrecs In Natural and Simulated Dr Environmentsmentioning
confidence: 99%